2012
DOI: 10.20360/g2f30j
|View full text |Cite
|
Sign up to set email alerts
|

Primary Students’ Book Club Participation

Abstract: This study is an examination of first grade students’ participation in Book Club at a high achieving, high poverty urban primary school in Detroit. In spite of the school’s high performing record, teachers are constrained by having to adhere closely to the pacing guide and the exclusive use of curriculum literature to preserve the school’s high achieving status. Irrelevant curriculum materials surrounding the themes “Keep Trying” and “Being Afraid” led to a teacher and researcher collaboration to use relatable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
7
1
6
Order By: Relevance
“…Este estudio confirma la relevancia que puede tener un club de lectura escolar en la mejora de la competencia literaria en, al menos, los cuatro ámbitos analizados: ha logrado estimular la comprensión literaria a través de sus procesos de diálogo (Gritter, 2011;Reed & Vaughn, 2012) Shaw, 2013) y ha desarrollado el gusto por la lectura en tiempo de ocio y el hábito lector de los participantes (McMahon, 1992;Goatley, Brock & Raphael, 1995;Johnsson-Smaragdi & Jönsson, 2006;Atwell, 2007;McKool, 2007;Whittingham, & Huffman, 2009;Barone, 2011;Gambrell, 2011;Hill, 2012;Reznitskaya, 2012;Kim & Quinn, 2013;Álvarez, 2015). Como han planteado Ballester e Ibarra (2009), la competencia literaria se adquiere a partir de la inmersión, de la interpretación y el disfrute del texto.…”
Section: Conclusionesunclassified
See 2 more Smart Citations
“…Este estudio confirma la relevancia que puede tener un club de lectura escolar en la mejora de la competencia literaria en, al menos, los cuatro ámbitos analizados: ha logrado estimular la comprensión literaria a través de sus procesos de diálogo (Gritter, 2011;Reed & Vaughn, 2012) Shaw, 2013) y ha desarrollado el gusto por la lectura en tiempo de ocio y el hábito lector de los participantes (McMahon, 1992;Goatley, Brock & Raphael, 1995;Johnsson-Smaragdi & Jönsson, 2006;Atwell, 2007;McKool, 2007;Whittingham, & Huffman, 2009;Barone, 2011;Gambrell, 2011;Hill, 2012;Reznitskaya, 2012;Kim & Quinn, 2013;Álvarez, 2015). Como han planteado Ballester e Ibarra (2009), la competencia literaria se adquiere a partir de la inmersión, de la interpretación y el disfrute del texto.…”
Section: Conclusionesunclassified
“…Por ello, concluimos que es urgente y relevante que los centros educativos se impliquen en el desarrollo de clubs de lectura escolares ya que puede ser concebido como uno de los recursos más potentes para favorecer la innovación en la didáctica de la literatura. Asimismo, también parece necesario transformar las prácticas de trabajo literarias habituales en las aulas y bibliotecas para abordar la lectura literaria desde una perspectiva de diálogo (Hill, 2012). Como ha planteado Ballester (2015), el desarrollo de la competencia literaria exige un larguísimo proceso que comprende desde el inicio en la etapa de primeros lectores hasta la etapa de sistematización, de reflexión y de desarrollo de las capacidades metaliterarias.…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…To address constraints manifest in high stakes testing pressures and satisfy state and national standards, Hollingworth (2011Hollingworth ( , 2007 recommended connecting existing reading units to real-world contexts, in which readers access real books and connect their home and school lives. Kersten & Pardo (2007), Certo (2011), Hill (2012, and Wall, Higgins & Smith (2005) demonstrated that curricular innovations are possible when facilitated through collaborative efforts. Kersten and Pardo (2007) collaborated with teachers who devised literature-based instructional strategies, in which they negotiated paced curriculum while linking elements of their best practice and emphasizing supplemental authentic literature.…”
Section: Negotiating Curricular Innovations and High Stakes Testing Pmentioning
confidence: 99%
“…Such peer interactions facilitate students develop higher-level thinking abilities to analyze, synthesize, and evaluate various information (Goatley, Brock, & Raphael, 1995). Studies have evidenced that peer-led discussion enhanced deep comprehension and students' ability to mediate personal connections and multiple perspectives (Hill, 2012;Hill, 2013). Through the process of exchanging opinions, students also become more competent in response-related skills necessary for discussions such as elaborating ideas of others and requesting clarification.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%